An Investigation To Look Into The Relationship Between Steatotic Liver Damage And Metabolic Syndrome. Problems: A Thorough Perspective On A Complicated Issue - Decai, Dai; Babu Natarajan, Satheesh (Journal of Neonatal Surgery, 2025)
More and more people are being affected by nonalcoholic fatty liver disease (the ailment), which affects more than 25% of the world's population and more than 60% of those at a higher risk. As part of metabolic syndrome, it raises the risk of developing specific illnesses related to the cardiovascular system and liver. Because NAFLD is a complicated illness with many associated comorbidities and difficulties, its treatment requires a multidisciplinary approach. But many medical experts are unsure about how to proceed after a diagnosis of non-alcoholic fatty liver disease (NAFLD), its comorbidities, and the severity of the condition and its potential consequences. Cirrhosis, inflexible simple steatosis, hepatocellular cancer, and cardiovascular disease are among of the conditions that may coexist with actively metabolizing non-alcoholic steatosis (NASH). It may be difficult to decide on the optimal diagnostic and treatment procedures due to the contradicting advice. In this article, researchers will review the history of NAFLD, its symptoms, and available treatments before shifting gears to talk about where researchers can see multidisciplinary care pathways going in the future.